An evaluation of fluid immersion therapy for the prevention of pressure ulcers. (December 2016) - Worsley, P.R.; Parsons, B.; Bader, D.L.
Abstract: Background: Individuals with impaired mobility can spend prolonged periods on support surfaces, increasing their risk of developing pressure ulcers. Manufacturers have developed mattresses to maximise contact area. The present study evaluated both the biomechanical and physiological responses to lying postures on a Fluid Immersion Simulation mattress. Methods: Seventeen healthy participants were recruited to evaluate the mattress during three prescribed settings of immersion (high, medium and low). Parameters reflecting biomechanical and physiological responses, and the microclimate were monitored during three postures (supine, lateral and high-sitting) over a 90 minute test session. Transcutaneous oxygen and carbon dioxide gas responses were categorised according to three criteria and data were compared between each condition. Findings: Results indicated that interface pressures remained consistent, with peak sacral values ranging from 21 to 27 mmHg across all immersion settings and postures. The majority of participants (82%) exhibited minimal changes in gas tensions at the sacrum during all test conditions. By contrast, three participants exhibited decreased oxygen with increased carbon dioxide tensions for all three immersion settings. Supine and high sitting sacral microclimate values ranged between 30.1–30.6 °C and 42.3–44.5% for temperature and relative humidity respectively. During lateral tilt there was a reduction of 1.7–2.5 °C and 3.3–5.3% in these values. The majority of participants reported high comfort scores, although a few experienced bottoming out during the high-sitting posture at the high immersion setting. Interpretation: Fluid Immersion Simulation provides an intelligent approach to increase the support area. Further research is required to provide evidence based guidance on the use of personalised support surfaces. Highlights: We assessed the biomechanical and physiological response to fluid immersion therapy. We measured the biomechanical and physiological response during three postures. The fluid immersion therapy provided high envelopment to redistribute pressures. In the majority of participants the sacrum remained perfused. Some bottoming out was observed during the high immersion mattress setting.